Grain-scale distribution of molybdenite polytypes versus rhenium contents: μXRD and EBSD data. (30th July 2019) - Plotinskaya, Olga Y.; Shilovskikh, Vladimir V.; Najorka, Jens; Kovalchuk, Elena V.; Seltmann, Reimar; Spratt, John
Abstract: Molybdenite from two porphyry copper mineralisation sites within the South Urals was studied by electron microprobe (EMPA), micro x-ray diffraction (μXRD) and electron backscattered diffraction (EBSD) methods. Elevated contents of rhenium (0.2 to 0.4, sometimes up to 1.1 wt.%) form linear zones from several to tens of micrometres wide and up to hundreds of micrometres long parallel to the elongation of molybdenite flakes. In most cases Re-rich zones are composed of the rhombohedral (3 R ) polytype of molybdenite, while the rest of the molybdenite flakes with ca. 0.1 wt.% of Re consist of hexagonal (2 H ) molybdenite. In rare cases Re-rich zones are confined to grain boundaries of molybdenite-2 H . It is shown that both μXRD and EBSD are the most appropriate tools to distinguish different polytypes within a single grain of molybdenite.